2006
DOI: 10.1073/pnas.0603236103
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for ligand promiscuity in cytochrome P450 3A4

Abstract: Cytochrome P450 (CYP) 3A4 is the most promiscuous of the human CYP enzymes and contributes to the metabolism of Ϸ50% of marketed drugs. It is also the isoform most often involved in unwanted drug-drug interactions. A better understanding of the molecular mechanisms governing CYP3A4 -ligand interaction therefore would be of great importance to any drug discovery effort. Here, we present crystal structures of human CYP3A4 in complex with two well characterized drugs: ketoconazole and erythromycin. In contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

40
725
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(767 citation statements)
references
References 32 publications
40
725
0
2
Order By: Relevance
“…One structure of the enzyme showed that CYP3A4 has a large active site with a peripheral progesterone binding site, which would be consistent with the peripheral effector binding site model, although no progesterone occupied the active site [21]. Another structure shows two ketoconazole drug molecules bound in the active site of CYP3A4 simultaneously, which would be consistent with the multi-substrate binding model and was observed previously in the CYP3A4 homolog, cytochrome P450 eryF (P450 eryF ) [20,23]. Neither structure provides conclusive evidence for the mechanism of cooperativity, since either the substrate was absent from the active site, the ligand was inhibitory, or the concentrations used can not be extrapolated to the solution experiments.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…One structure of the enzyme showed that CYP3A4 has a large active site with a peripheral progesterone binding site, which would be consistent with the peripheral effector binding site model, although no progesterone occupied the active site [21]. Another structure shows two ketoconazole drug molecules bound in the active site of CYP3A4 simultaneously, which would be consistent with the multi-substrate binding model and was observed previously in the CYP3A4 homolog, cytochrome P450 eryF (P450 eryF ) [20,23]. Neither structure provides conclusive evidence for the mechanism of cooperativity, since either the substrate was absent from the active site, the ligand was inhibitory, or the concentrations used can not be extrapolated to the solution experiments.…”
Section: Introductionsupporting
confidence: 85%
“…The recently solved x-ray crystal structures of CYP3A4 have shed some light on the molecular basis of the first two models [20][21][22]. One structure of the enzyme showed that CYP3A4 has a large active site with a peripheral progesterone binding site, which would be consistent with the peripheral effector binding site model, although no progesterone occupied the active site [21].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the human genome, 57 genes have been found to code for CYPs [2]. The main CYPs implicated in drug metabolism, such as CYP3A4, CYP2C9 or CYP2D6, and those responsible for the biosynthesis of steroid hormones have been extensively studied, and several x-ray structures of human CYPs have been recently published [3][4][5][6][7][8][9][10]. Much less is known about more recently discovered human CYPs such as CYP2J2 [2,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, many enzymes are catalytically promiscuous, and they can metabolize structurally distinct substrates or convert a single substrate to multiple products. It is increasingly well-appreciated that functional promiscuity (4) is important for the evolution of new protein functions (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), the in vitro engineering of biocatalysts (16)(17)(18)(19), and drug metabolism (8,(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%